Molecular basis and outcomes of atypical haemolytic uraemic syndrome in Czech children - Štolbová, Šárka; Bezdíčka, Martin; Seeman, Tomas; Prohászka, Zoltán; Csuka, Dorottya; Hrachovinová, Ingrid; Burkert, Jan; Šimánková, Naděžda; Průhová, Štěpánka; Zieg, Jakub (European journal of pediatrics, 2020)
Atypical haemolytic uraemic syndrome is an ultra-rare, life-threatening disease. Causative variants in genes that encode complement factors can be identified in 40-70% of cases. We performed genetic analysis of 21 Czech children with atypical haemolytic uraemic syndrome. Genetic or acquired predisposition to the disease was identified in the majority of our patients: CFHR1 and CFHR3 deletions in 14/21 (67%; 13 of them were positive for anti-complement factor H antibodies), variants in complement genes or DGKE in 13/21 (62%). Multiple genetic findings were identified in eight patients (38%). The incidence of atypical haemolytic uraemic syndrome in the Czech paediatric population was estimated to be 0.092 (CI 0.053-0.131) cases per million inhabitants and 0.92 (CI 0.53-1.32) cases per 100,000 births for the entire reporting period. Ten patients were initially treated with plasma exchange and eight with eculizumab or with a combination of eculizumab and plasma exchange. At the last follow-up, 20 patients were alive and one patient had end-stage renal disease.Conclusion: The incidence of atypical haemolytic uraemic syndrome in the Czech paediatric population corresponds to the reported incidence in Europe. We detected the unusually high rate of CFHR1/CFHR3 deletions associated with anti-complement factor H antibodies in Czech paediatric patients. Treatment by eculizumab led to superior outcomes and prevention of the disease relapses compared with plasma exchange therapy. Our results may help to understand the polygenic nature of atypical haemolytic uraemic syndrome as a disease that results from a combination of various risk factors. What is Known: • Atypical haemolytic uraemic syndrome (aHUS) is considered a polygenic and multifactorial disease. Genetic predisposition to aHUS is identified in 40-70% of children. • Anti-complement factor H antibodies are usually found in 6-25% of affected children. What is New: • Potentially causative genetic or acquired factors were confirmed in the majority of patients. The prevailing finding was the unusually high rate of CFHR1/CFHR3 deletions associated with anti-complement factor H antibodies (62% of patients). • The incidence of aHUS in Czech children is 0.092 (CI 0.053-0.131) cases per million inhabitants and 0.92 (CI 0.53-1.32) cases per 100,000 births for the entire reporting period.
Keywords: Atypical haemolytic uraemic syndrome; Europe; Next-generation sequencing; Česká republika; atypický hemolyticko-uremický syndrom; Evropa; Anti-complement factor H antibodies; Alternative complement pathway; Czech Republic; dítě; DGKE; Child; Humans; rizikové faktory; výměna plazmy; Risk Factors; Children; Atypical Hemolytic Uremic Syndrome; Plasma Exchange; lidé